The Role of Local Government Policies in Reducing Extreme Poverty: A Case Study of Pinogaluman Subdistrict - M, Nursafitra; P, Resky Amalia.; Onasis, Andi; Walahe, Dewi (Journal of Posthumanism, 2025)
This research aims to analyze government policies in overcoming extreme poverty in Pinogaluman District, North Bolaang Mongondow Regency, with a focus on the dynamics and process of implementing these policies. Using a qualitative approach with a subjective exploration strategy, this research relies on collecting primary data through interviews with the sub-district head, sub-district secretary and community leaders, as well as secondary data from related documents. Data collection techniques include direct observation, in-depth interviews, and documentation. Data analysis was carried out interactively, through stages of reduction, presentation and drawing conclusions, to identify the phenomenon of extreme poverty and its correlation with government policy. The research results show that the government’s policy model for overcoming extreme poverty in Pinogaluman District has been working well, as shown through four main indicators: (1) Communication, where effective communication has been established between the government and the community, even though there are challenges to data accuracy; (2) Resources, which are managed wisely through a holistic and community-based approach; (3) Disposition, which involves rapid government response and local community participation; and (4) Bureaucratic structure, which emphasizes cooperation between government and society as well as continuous evaluation. This research concludes that government policies in reducing extreme poverty have had a significant positive impact, but further efforts are needed to increase the effectiveness of existing programs.